New Role of Pd Hydride as a Sensor of Surface Pd Distributions in Pd−Au Catalysts. Issue 3 (11th December 2019) - Guan, Erjia; Foucher, Alexandre C.; Marcella, Nicholas; Shirman, Tanya; Luneau, Mathilde; Head, Ashley R.; Verbart, David M. A.; Aizenberg, Joanna; Friend, Cynthia M.; Stacchiola, Dario; Stach, Eric A.; Frenkel, Anatoly I.
Abstract: Isolated or contiguous, the surface distributions of Pd atoms in the Pd−Au bimetallic nanoparticle (NP) catalysts often influence activity and selectivity towards specific reactions. In this study, we used a concomitant Pd hydride formation upon H2 exposure as a probe of presence of contiguous Pd regions in bimetallic NPs. For demonstrating this method, we prepared silica supported monometallic Pd and bimetallic Pd−Au NPs with a Pd/Au ratio of 25/75 (Pd25 Au75 ) and used X‐ray absorption spectroscopy, scanning transmission electron microscopy and infrared spectroscopy to detect and quantitatively analyze the Pd hydride regions. This work provides a new approach to characterizing intra‐particle heterogeneities within the bimetallic NPs at ambient temperature and pressure. Abstract : Isolated or contiguous : STEM‐EDS and EXAFS of Pd25 Au75 nanoparticles supported on RCT SiO2 . Contiguous Pd assembles on the surface of the bimetallic nanoparticles expand upon H2 exposure at room temperature.